Motivasi Siswa Peserta Ekstrakurikuler Futsal di SMP Negeri 22 Surabaya - Muchammad Afandi; Setiyo Hartoto; Sasminta Christina Yuli Hartati; Bayu Budi Prakoso (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Students' motivation in participating in futsal extracurricular sports can be driven by various factors. Understanding this motivation is important for extracurricular managers and teachers to be able to provide the right support and facilities, as well as create an environment that encourages students to actively participate and get the maximum benefits from futsal extracurricular activities. This research uses quantitative research with a survey approach to describe the motivation of extracurricular students at SMP Negeri 22 Surabaya. The data analysis technique is statistical descriptive with data collection techniques using questionnaires. From the reliability test, it is said that it is reliable and the validation test of the questionnaire item is valid. The results of the study showed an average score of 55.53, a middle score of 56, a mode value of 57, a standard deviation value of 5.754, a minimum score of 43, a maximum score of 68, a total of 43 respondents and a total score of 2388. Students participating in futsal extracurricular at SMP Negeri 22 Surabaya which are in a very high group there are 3 people or 6.98 percent, students with high motivation there are 35 people or 81.40 percent, and students with medium motivation there are 5 people or 11.63 percent Student motivation that those who take part in futsal extracurricular at SMP Negeri 22 Surabaya are in the category of high motivation or a percentage of 69.